Competition, innovation, and competition law: Dissecting the interplay - Wolfgang Kerber (Philipps-University Marburg, School of Business and Economics, 2017)
The digital revolution has reinvigorated the discussion about the problem how to consider innovation in the application of competition law. This raises difficult questions about the relationship between competition and innovation as well as what kind of assessment concepts competition authorities should use for investigating innovation effects, e.g., in merger cases. This paper, on one hand, reviews briefly our economic knowledge about competition and innovation, and claims that it is necessary to go beyond the limited insights that can be gained from industrial economics research about innovation (Schumpeter vs. Arrow discussion), and take into account much more insights from innovation research, evolutionary innovation economics, and business and management studies. On the other hand, it is also necessary to develop much more innovation-specific assessment concepts in competition law (beyond the traditional product market concept). Using the example of assessing innovation competition in merger cases, this article suggests to analyze much more systematically the resources (specialized assets) that are necessary for innovation. This concept is directly linked to the new discussion about the Dow/DuPont case in the EU and about data as necessary resource for (data-driven) innovation.
Keywords: K21; L12; L41; O31; 330; Competition; innovation; competition law; merger control; innovation market